Conceptualizing Artificial Intelligence in the Indonesian Education Systems and Reciprocity with AI-Based Curriculum - Alamsyah, Nurwahyu; Neal, Dale (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
This study employs a Systematic Literature Review (SLR) to analyze the curriculum challenges in Indonesia and explore the potential AI-driven solutions to improve the education systems. The findings reveal that conventional teaching methods, lack of project-based learning (PBL), limited technology integration, and rigid learning approaches are among the most critical issues, leading to low student engagement and an imbalance between hard and soft skills. To address these challenges, AI technologies such as adaptive learning, formative assessments, and AI-powered virtual classrooms can be integrated to enhance personalized and competency-based learning. The findings suggest that by adopting AI-driven strategies, Indonesia can modernize its curriculum, enhance educational effectiveness, and align with global standards. This study contributes to evidence-based policymaking by offering insights into AI adoption in education and proposing a roadmap for a technology-integrated, student-centered learning system.